Sistem Vertikultur Terhadap Pertumbuhan Tanaman Bayam Merah (Amaranthus tricolor L) Varietas Mira dengan Pemberian Fermentasi Air Kelapa Tua (Cocos nucifera) - Rila Fauzila; Wagiono Wagiono; Bastaman Syah; Hayatul Rahmi (Peneliti.net, 2021)
Verticulture is a method of farming both indoors and outdoors that utilizes limited land. One of the plants that can be cultivated with a verticulture system is red spinach. Red spinach is an annual plant, usually grows in tropical areas and is an important vegetable crop for people in lowlands. This research was conducted in March - April 2021. This study used a non-factorial randomized block design consisting of 7 treatments and 4 replications : A0- kontrol (0 ml/l), A0+ kontrol (POC NASA 6 ml/l), A1 (100 ml/l), A2 (200 ml/l), A3 (300 ml/l), A4 (400 ml/l), dan A5 500 (500 ml/l). The purpose of this study was to determine the effect of fermentation of old coconut water on the growth and yield of red spinach and to find out at what concentration the fermentation of old coconut water gave the best results for red spinach with a verticulture system. The results showed that the plant height, number of leaves, leaf area, wet weight and dry weight obtained the highest average value in the A0-control treatment (0 ml/l), while the lowest value was obtained in the A5 treatment (500 ml/l). The fermentation concentration of old coconut water had no significant effect on the parameters of plant height, number of leaves, leaf area, wet weight and dry weight of red spinach plants.